2018
DOI: 10.1080/00015385.2017.1421300
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization-associated disability in older adults with valvular heart disease: incidence, risk factors and its association with care processes

Abstract: Half of the older adults with VHD developed HAD. The results indicate a potential association between HAD and care processes, which could be used as quality measures and intervention targets. Validation in larger cohort studies is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…Moreover, there was a large difference between the length of hospital stay. While the length of stay was 23 days in average for our study, it was 4 to 13 days in the previous studies [20][21][22]. Thus, patients in our study may have undergone more rehabilitation compared to patients in the previous studies, which may have contributed to the lower prevalence of HAD.…”
Section: Plos Onementioning
confidence: 50%
See 1 more Smart Citation
“…Moreover, there was a large difference between the length of hospital stay. While the length of stay was 23 days in average for our study, it was 4 to 13 days in the previous studies [20][21][22]. Thus, patients in our study may have undergone more rehabilitation compared to patients in the previous studies, which may have contributed to the lower prevalence of HAD.…”
Section: Plos Onementioning
confidence: 50%
“…valvular heart disease and found that 51.9% of their subjects developed HAD [20]. Other studies reported the prevalence of HAD as 41% and 33% among older adults admitted to general medicine and cardiac care unit, respectively [21,22].…”
Section: Plos Onementioning
confidence: 98%
“…This theory was developed by integrating evidence from (1) a systematic review and meta-analysis on the effectiveness of geriatric co-management programmes, 18 (2) an international Delphi study that aimed to find consensus on appropriate and feasible structure, process and outcome indicators for the evaluation of in-hospital geriatric co-management programmes 21 and (3) an exploratory prospective cohort study in hospitalised patients with cardiac conditions to determine the incidence of in-hospital functional decline, the associated risk factors and the link with care processes. 22 Additionally, we developed a clinical prediction model that identifies patients who are at risk for developing functional decline during hospitalisation. This risk prediction model was built based on data from the precohort of this intervention study, and will be used to identify patients in need for geriatric co-management, that is, patients with an increased risk for functional decline (submitted manuscript).…”
Section: Methodsmentioning
confidence: 99%
“…We assumed a minimal important difference of 1 mean point on the Katz ADL and a SD of 3 points on the Katz ADL with equal groups, based on observations in a pilot study. 22 This equals a standardised effect size of 0.33 (Cohen’s d) and indicates a low-to-moderate effect size. Therefore, a total of 159 patients are needed per group (α=0.05, Power=0.8, two-sided test), accounting for 10% missing data.…”
Section: Methodsmentioning
confidence: 99%
“…We assumed a minimal important difference (MID) of one point on the Katz ADL between the intervention groups at hospital discharge, with a standard deviation of three points (based on observations in a pilot study). 11 Accounting for 10% missing data, 159 patients were needed per group (alpha = 0.05, power = 0.8, two-sided test). We aimed to recruit 227 patients per group because we expected that 30% of recruited patients would be at low risk for functional decline and not be eligible for follow-up.…”
Section: Sample Sizementioning
confidence: 99%